Future Flood Management and Control Policies: A Comparative Study of Europe and Indonesia - Pramudhian Firdaus; Raldi Hendro Koestoer (MO.RI Publishing, 2022)
Human activities have caused changes in land use, climate, and rainfall in the last few centuries, one of which is marked by an increase in the occurrence of floods. Flood events in Europe in the period 1998 – 2009 caused more than 1100 damage and displacement of more than one million people. To overcome this, the European Commission (EC) published the Flood Directive 2007/60/EC (FD) with the aim of reducing and managing flood risks for human health, the environment, natural resources, and economic activities. This paper aims to determine the policies and management of the government and the community towards flood disaster management in the future from the results of research conducted in countries in Europe (Portugal, Slovenia, Serbia, and Bosnia & Herzegovina) and then a comparison is made with conditions in Europe. Indonesia to see the differences and similarities in the perception of the government and the public regarding policies and management of flood events that occur in Indonesia. The provision of infrastructure requires not only technical and financial capacity but also appropriate coordination between different government agencies. Disaster risk reduction through appropriate land use planning and control is an important instrument for securing urban areas from flooding (as a result of a case study in Indonesia). Perceptions of future flood management and control policies require serious attention from various lines, especially within the government as policy makers and the community as implementers in the field.